1986
DOI: 10.2136/sssaj1986.03615995005000050044x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sediment Movement at Low Erosion Rates Using Cesium‐137

Abstract: New and innovative methods for measuring soil loss and its impact on productivity are needed to accurately assess the value of soil lost by erosion. Cesium‐137 (137Cs), a radionuclide from nuclear weapons tests which is strongly adsorbed to clay, can be used to trace sediment movement. Measurements of 137Cs concentrations in uneroded soils across the southern United States indicated that the 137Cs input was proportional to the average annual precipitation. Distribution of 137Cs within the profile was related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…The greater CV on the cultivated plot would contribute more to the output uncertainty of the soil loss estimates. The CV on cultivated sites was reported to be much greater than those on reference sites, resulting from localized erosion and microtopographic changes caused by tillage operation (Lance et al, 1986;Sutherland, 1994). The greater variability in 137 Cs inventory on the measuring site necessitates a greater number of independent samples to be taken in order to afford reliable estimates of the mean inventory and subsequently mean soil redistribution rate for the area.…”
Section: Sensitivity and Uncertainty Analyses With The First Order Apmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater CV on the cultivated plot would contribute more to the output uncertainty of the soil loss estimates. The CV on cultivated sites was reported to be much greater than those on reference sites, resulting from localized erosion and microtopographic changes caused by tillage operation (Lance et al, 1986;Sutherland, 1994). The greater variability in 137 Cs inventory on the measuring site necessitates a greater number of independent samples to be taken in order to afford reliable estimates of the mean inventory and subsequently mean soil redistribution rate for the area.…”
Section: Sensitivity and Uncertainty Analyses With The First Order Apmentioning
confidence: 99%
“…Sutherland (1994) reported that spatial variability across a gentle slope within the cultivated field was 55% greater than that within a nearby undisturbed field. Lance et al (1986) reported that the mean variance of 137 Cs inventories averaged over 17 transects running along contour lines in a cultivated slope plot was 99.6 (Bq 2 core −2 ), whereas that averaged over nine transects in an adjacent native tallgrass prairie plot was 34.8 (Bq 2 core −2 ), showing 1.9 times increase by tillage operation and localized soil erosion. The increased variance on an eroding site would substantially reduce the sensitivity of the 137 Cs technique in detecting soil erosion (Kirchner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The other area of concern is sampling design and the number of samples to be collected from uneroded reference (control) locations, and from disturbed SRD locations. At present, systematic-aligned grid-based sampling is the most common framework for 137Cs investigations in disturbed areas (Lance et al, 1986;Martz, 1986;Pennock and de Jong, 1987;Sutherland, 1994). This sampling design has proved to be very effective for field implementation and additionally it provides a solid framework for rigorous geostatistical investigations (Busacca et al, 1993;.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Salemme and Olson 2014;Olson et al 2014cOlson et al , 2013aOlson et al , 2011Kumar et al 2012;Gennadiyev et al 2010) reported that the conversion of prairie to agricultural land for 90 to 140 years resulted in a loss of between 20% and 51% of the SOC stock, and conversion of forest to agricultural land for 100 to 150 years resulted in a SOC stock loss of 10% to 52%. Thus, it is essential to understand the effects of soil erosion in the context of agricultural use, especially in intensive agriculture production systems, where erosion process becomes a driver in establishing C sources and loss as CO 2 rather than a significant contributor to soil C retention within a land unit (Lance et al 1986). Olson et al (2013b) and Young et al (2014) showed that nearly level (<1%) upland agricultural plots were also subject to erosion, transport, and deposition of SOC-rich sediments.…”
mentioning
confidence: 99%